Agricultural marketing in India - Singhal, A.K. (New Delhi, 1989)
During the last two decades, quite a few studies published and unpublished, have gone into the detailed marketing structure, price differences and market integration of certain crops in some regions. However most of the important crops in most of the producing regions, of the country have not been subjected to such analysis. It is generally expec ted that the marketing structure and sys tems has been undergoing steady changes under the impact of developing roads communication in rural areas, greater flow of information as well as govern mental regulation of marketing activity to ensure freer and informed competi tion. Nevertheless, it cannot be said that marketing system for most agricul tural commodities and in most regions has progressed equally. An attempt is, therefore, made here to examine the nature and impact of the governmental measure at regulation of agricultural markets in the states.
Keywords: Agriculture